1980
DOI: 10.1002/path.1711310103
|View full text |Cite
|
Sign up to set email alerts
|

The production of heterotopic calcification by certain chemical salts

Abstract: The subcutaneous injection of small quantities of LaCl3 and CeCl3 was followed by calcification of the dorsal fascia in mice. The calcification reaction was shown by separate positive histochemical tests for calcium ions (the chloranilic acid reaction) and phosphate (the von Kossa reaction). The injection of cadmium chloride and stannous salts caused damage to and a positive von Kossa reaction in the fibres of the panniculus carnosus muscle. The significance and specificity of the histochemical tests was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…* or the mineralized patches of skin found in calciphylaxis or calcergy. [3][4][5] In these instances, the collagen-mineral composite is marked by a brittle nature rather than by the hardness and strength of normally calcified tissues. This marked fragility frequently leads to complications of skeletal growth or other possibly severe consequences in calcification.…”
Section: Introductionmentioning
confidence: 97%
“…* or the mineralized patches of skin found in calciphylaxis or calcergy. [3][4][5] In these instances, the collagen-mineral composite is marked by a brittle nature rather than by the hardness and strength of normally calcified tissues. This marked fragility frequently leads to complications of skeletal growth or other possibly severe consequences in calcification.…”
Section: Introductionmentioning
confidence: 97%
“…S E L Y E (1962) indicated that the trichlorides of the rare earth elements lanthanum and cerium were capable of causing local calcification when injected into the subcutaneous tissues of the rat (local calcergy). This observation was confirmed for the mouse by McClure (1980). Haley and Upham (1963) have also demonstrated calcium salts in granulomas induced by the intradermal injection of several lanthanides in the guinea-pig.…”
mentioning
confidence: 58%
“…17,18 Subsequently, McClure et al tested the calcergenic effect of lanthanides (including GdCl 3 ) in the mouse, and obtained a similar reaction pattern. 41 Johansson et al also have demonstrated that intravenous injections of lanthanum chloride (LaCl3) produces hypercalcemia and hyperphosphatemia, a milieu proven to be conducive to the deposition of calcium phosphate. 42 While these reports, in aggregate, indicate that calcification and lesions of CUA may be induced by injection of metal salts into the skin, a more detailed understanding of the mechanism of CUA in vivo in humans including an analysis of tissue content of metals has never been performed previously.…”
Section: Discussionmentioning
confidence: 99%